Философия: учебник для вузов / Г. И. Иконникова, В. Н. Лавриненко [и др.] ; ред. В. Н. Лавриненко - Лавриненко Владимир Николаевич (Institutiones, 1998)
Экземпляры: аб. (1999) / Инвентарный номер: 41369 / Цена: / Сис.шифр: 87 / Авт.знак: Ф 56 / ГРНТИ: 02.01 / ББК: 87я73